Managing global engineering networks part II: Case studies and directions for the future research. (February 2014) - Zhang, Yufeng; Gregory, Mike; Shi, Yongjiang
The second part of this article reports our query into the essential characteristics of effective engineering networks in the current business environments through case studies focusing on engineering design, manufacturing engineering, and engineering services. The engineering networks of four global leading companies were studied to refine, enrich, and extend the preliminary understandings gained from the first part of this article. The case studies suggested essential characteristics of effective engineering networks in four main areas, including (1) efficient engineering processes, (2) effective engineering learning, (3) flexible engineering resources, and (4) digital engineering environment. This contributes to the theoretical understanding of international engineering operations by bridging a missing link between the engineering network theories and the unique nature of engineering. It is expected that the findings can help managers to improve the performance of their engineering networks and facilitate the effective interface management between engineering and other functional areas.